A Comparison of Educational Methods—Lecture (PPT) versus Visual—Regarding Reproductive Health Knowledge among Adolescents at SMK Bhakti Asih Purwakarta - Dita Humaeroh; Tia Suciati; Husnul Chotimah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Reproductive health, like health in general, is a fundamental human right. Achieving it requires accurate and comprehensive knowledge regarding reproductive health. Such knowledge is acquired through various channels, one of which is education. This study employed a quasi-experimental design—specifically a two-group pretest-posttest design—involving 76 respondents selected via total sampling. The experimental group utilized visual media, while the control group received instruction through lectures (PowerPoint presentations). The results indicate a significant difference between the use of visual media (videos) and lectures (PowerPoint) in improving reproductive health knowledge among adolescents. The group receiving education via visual media achieved higher knowledge scores than the lecture group, with a p-value of 0.016 (< 0.05). Thus, the use of visual media is more effective than the lecture method in enhancing adolescents' reproductive health knowledge. These findings support the use of visual media to improve adolescents' knowledge of reproductive health.